Fatherhood in the Nordic welfare states : comparing care policies and practice - Guðný Björk Eydal; Rostgaard, Tine (Policy Press, 2015)
The Nordic countries are known worldwide for their extensive welfare system and gender equality, which enables both parents to hold jobs, earn money, and care for their children. In this volume, scholars from the Nordic countries, as well as from the United States and the UK, explore the effects of these policies on fatherhood, and how the policies that support it contribute to shaping and influencing the image, role, and practice of fathers in a diversity of family settings.